Optimization of Guidance and Counseling Services: Analysis of Guidance and Counseling Management Concepts and Problems and Solutions in Education - Fika Dwi Mulia; Neviyarni S; Yarmis Sukur (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This literature-based study shows the importance of competent BK management for the efficiency and effectiveness of services. This includes planning, organizing, implementing, monitoring, and evaluating; separation of work, order, discipline, and unity of command are determining elements of successful BK management; various school staff members must be involved in providing guidance and counseling services, taking into account available resources. In order to improve the quality of services, this study proposes creative strategies to answer ideas and problems regarding the management of guidance and counseling (BK) services in schools. Adequate infrastructure is needed to support the Behavior Key (BK) program, which must be designed with students' needs in mind and integrated into the curriculum. Accountability and supervision are needed to ensure the achievement of expected results, and effective guidance and counseling not only helps students develop their independence and character but also increases public trust in the school's ability to provide these services. The results of this study are that the program for providing advice and counseling services will not be implemented if it has an effective, clear, systematic, and focused management structure. Management actions that provide counseling and advice must be adjusted to the role that allows management to achieve successful implementation results.